Hidrox® Counteracts Cyclophosphamide-Induced Male Infertility through NRF2 Pathways in a Mouse Model - Roberta Fusco; Angela Trovato Salinaro; Rosalba Siracusa; Ramona D'Amico; Daniela Impellizzeri; Maria Scuto; Maria Laura Ontario; Roberto Crea; Marika Cordaro; Salvatore Cuzzocrea; Rosanna Di Paola; Vittorio Calabrese (MDPI AG, 2021)
Background: Every year, men use cyclophosphamide to treat various cancers and autoimmune diseases. On the one hand, this chemotherapy often has the beneficial effect of regressing the tumor, but on the other hand, it leads to infertility due to excessive oxidative stress and apoptosis in the testes caused by its metabolite, acrolein. Methods: The objective of this study was to evaluate the beneficial power of a new compound called Hidrox®, containing 40-50% hydroxytyrosol, in counteracting the damage related to fertility induced by cyclophosphamide. The study was conducted using a single intraperitoneal injection of cyclophosphamide at a dose of 200 mg/kg b.w, in distilled water at 10 mL/kg b.w. The treatment was administered via the oral administration of Hidrox® at a dose of 50 mg/kg. Results: Our study confirms that the use of cyclophosphamide causes a series of sperm and histological alterations strongly connected with oxidative stress, lipid peroxidation, and apoptosis. Conclusion: Our results demonstrate for the first time that Hidrox® protects testes from CYP-induced alterations by the modulation of physiological antioxidant defenses.